Analisis Pembelajaran bagi Siswa Disleksia dan Disgrafia di SDN Pegadungan 11 Pagi - Nurfadhillah, Septy; Kamilah, Nur; Faizah, Annisa Nur; Lestari, Dewi Rachma; Lestari, Bela; Nugrahanti, Isnaini; Rahmawati, Nia; Fatimah, Rina Siti Nur (YASIN, 2021)
The purpose of this study was to find out how the learning process of students with learning difficulties in reading (dyslexia) and learning difficulties in writing (dysgraphia) was determined. This type of research approach is qualitative research. The research subjects were 3rd grade teachers. Data collection techniques used interviews and documentation. The results showed that there were students who had specific learning difficulties, namely reading difficulties (dyslexia) and writing difficulties (dysgraphia). Because these students cannot speak and use sign language to communicate with the teacher. During writing activities, the teacher usually does picture-matching activities, with the aim that students can more easily understand and understand learning. Based on the results of this study, it can be concluded that the learning given to dyslexic and dysgraphia students at SDN Pegadungan 11 Pagi is almost the same as regular students.